A New Vestibular Stimulation Mode for Motion Sickness With Emphatic Analysis of Pica - Zhang, Zhi-Hao; Liu, Li-Peng; Fang, Yan; Wang, Xiao-Cheng; Wang, Wei; Chan, Ying-Shing; Wang, Lu; Li, Hui; Li, Yun-Qing; Zhang, Fu-Xing (Frontiers in Behavioral Neuroscience, 2022)
Motion sickness (MS) was frequently introduced for rodents in research work through passive motion that disturbed vestibular signals in the context of visual and aleatory proprioceptive inputs. This type of MS with conflicted signals was built upon neural activities relating to circuits entangling multiple sensory modalities. From reductionism, a lab setup to elicit rat MS via vestibula-only stimulation was configured as a step for studying MS in connection with dissecting the vestibular component causally related to MS. Each individual animals was blinded to light with a custom-made restrainer, and positioned at an inclination of 30º for otolith organs to receive usual actions by gravitoinertial vector. Following a two-hour double-axis (earth-vertical) rotation involving angular acceleration/deceleration, a suit of behaviors characterizing MS was observed to be significantly changed including pica (eating non-nutritive substance like kaolin), conditioned taste avoidance and locomotion ( P < 0.05). Notably, for statistical hypothesis testing, the utility of net increased amount of kaolin consumption as independent variables in data processing was expounded. In addition, Fos-immunostained neurons in vestibular nucleus complex were significantly increased in number, suggesting the rotation-induced MS was closely related to vestibular activation. In summary, our work indicated that the present setup could effectively elicit MS which might be attributable to disturbance of vestibular signals in rat, with well-controled proprioceptive inputs and lacking visual cues.